CITRA SRIKANDHI DALAM CERITERA MAHABARATA (Pencitraan Nilai -Nilai Kewanitaan dalam Budaya Jawa ) - mamik Widyastuti (Institut Seni Indonesia Surakarta, 2007)
One of art forms capable for being used as the source of moral values in lift is Javanese shadow puppet because it contains various kinds of principles and ethic values. Indonesia people can make use of the principles and values to survive. The glorious principles and values made use of Indonesian people (espetialIy the Javanese) have existed since the old days.S rikandhi, one of female figures in the Mahabarata, is often thought of as an ideal figure because this female figure has the personality that is suitable for a model for responsibility, discipline, bravery, skills, and leadership. She is willing to put her own interest a side for the sake of the interest of others or her country. S rikandhi’s character has the image of femininity value.Javanese femininity value in the figure of Srikandhi is different from gender and feminism at issue which tend to think that Javanese women are always positioned as subordinate, weak and hopeless. The figure of Srikandhi projects an image of femininity value which positions women as strong characters, having strong potential as resources and not subordinate to men. Gender and feminism at issue aimed at Javanese women are strongfy rejected Srikandhi becomes the figure who presents the rejection of the issue through the estbetic image morally and artistically.Keywords: Srikandhi, Women, Value